ΔCT Value of Amplified Refractory Mutation System Predicts Efficacy of EGFR-TKIs in Advanced Non–Small-Cell Lung Cancer: A Multi-Center Retrospective Study - Chen, Min; Huang, Wenqi; Yang, Dongyong; Huang, Jincheng; Li, Gong; Wang, Xiaoqing; Xiao, Nanjie; Zhang, Weijian; Guan, Jian; Wang, Shuang; Liu, Laiyu (Frontiers in Molecular Biosciences, 2021)
Abstract Purpose This multi-center retrospective study was to determine whether the ΔCT value of Amplified Refractory Mutation System (ARMS) predicts the efficacy of epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) in EGFR-mutant advanced non-small-cell lung cancer (NSCLC). Patients and methods Patients harbored an exon 19 deletion (19Del) or L858R mutation detected by Amplified Refractory Mutation System (ARMS), previously received treatment of EGFR-TKIs as a monotherapy were enrolled. A total of 108 NSCLC patients in four hospitals were enrolled. We divided the patients into high delta Cycle Threshold (ΔCT) group (Group H) and low ΔCT group (Group L) by media ΔCT value. The primary outcome was progression-free survival (PFS). Univariate analysis and multivariable regression were applied to compare the PFS between the groups. Result In the 108 patients we enrolled, 54 were in group L and 54 were in group H. Patients’ demographics and clinical characteristics including age, sex, smoking history, pathology, mutation sites, TNM stage, line of TKIs therapy were not significantly difference between group L and group H. The Median PFS was 11.0 months in group L and 7.4 monthsin group H and the difference showed statistically significant (P<0.001). Moreover, the ORRs in group L was significant higher than the group H (63.0% vs 35.2%, P=0.004). The median OS was 24.8 months in group L and 20.5 months in group H but showed not statistically significant (P=0.094). Conclusion ΔCT value of ARMS could be an efficacy predictor for EGFR-TKIs treatment in advanced EGFR-mutant NSCLC.